Origins, production, and utilization of cassava in Burkina Faso, a contribution of a neglected crop to household food security - Guira, Flibert (Food Sci Nutr, 2016)
Cassava (Manihot esculenta Crantz) is a food plant introduced in Africa from America by the Portuguese in 1558. The objective of this study is to establish cassava origins, production, and utilization in Burkina Faso. The investigation was carried out in the regions of Center West, Cascades, Boucle du Mouhoun, Hauts Bassins, South West, and Center East of Burkina Faso. Eighteen cassava processing units and 226 farmers in 57 communities from the selected regions have been involved in the survey. The investigation showed that cassava was introduced to Burkina Faso, former Upper Volta from the costal countries, Gold Coast (now Ghana), by both local traders and the Roman Catholic White missionaries. This happened between the second half of the 19th century and the beginning of the 20th century. The main variety introduced was Banfti. Some improved varieties like V5 (94/0270), Banké (V2), 68.61, 30572, KTMA developed by research are now available and used by farmers along with the traditional varieties like manchien, santidougou, tchinda yaar, léo. The cases of intoxication evoked by some farmers are evidence that some of those varieties may have a high level of cyanohydric acid content. Cassava is available all the year throughout the country. But the top of cassava production is reached in July. Most of the small‐scale farmers (98%) grow cassava both for household use and as income generator. About 83.92% of cassava farmers have less than 10 tons as annual production and only 1.72% of them can produce more than 100 tons. The main food products based on cassava found in communities are raw roots, boiled roots, roasted roots, tô, attiéké, tapioca, ragout, beignets, boiled leaves, soup (with leaves), cassava juice, etc. And the main cassava‐processed products in the processing units are attiéké, gari, tapioca, and flour. Cassava contributes greatly to household food security during food shortage period. It sustains families for weeks as food and is also exchanged with other foods or sold to buy food or meet household needs.